Children’s Legal Protection in Landfill-Affected Communities: State Responsibility Analysis in Makassar City - Ririn Nurfaathirany Heri; Maya Kasmita; Muhammad Aswan; Andi Mutya; Siti Fatimah Nur Syachriani (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Landfill-affected communities face compounded socio-economic challenges that extend beyond technical environmental management and disproportionately affect children and other vulnerable groups living in surrounding areas. Objective: This study examines the normative framework for the legal protection of children and vulnerable groups surrounding the Tamangapa Landfill in Makassar City and critically evaluates the responsibilities of the state and local government in mitigating the associated socio-economic impacts. Methods: This study employs a normative-empirical method with legislative and conceptual approaches, supported by empirical data on landfill management conditions and the social life of surrounding communities. Results: The findings indicate that the management of the Tamangapa Landfill, which is still dominated by an open dumping system, combined with high waste volumes and the community’s economic dependence on informal waste-related activities, has created structural vulnerabilities for children and vulnerable groups. These include increased health risks, the normalization of child labor, and limited access to basic services. Normatively, this condition reflects the suboptimal fulfillment of state and local government obligations as duty bearers in ensuring children’s rights and the protection of vulnerable groups, as mandated in the 1945 Constitution, the Child Protection Law, and applicable waste management legislation. Conclusion: This study underscores that sustainable landfill governance must be integrated with obligations to protect children and vulnerable groups, necessitating policy reforms that embed human rights standards within waste management frameworks.